Finance for sustainability in a turbulent economy - Rafay, Abdul, 1973- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book provides international financial strategies to achieve sustainable business practices within a turbulent economy, covering topics such as low-cost clean energy for transportation, energy alternatives, and policy-based cost solutions"--